The Exploration of Mathematical Objects in Anime Series Reviewed from Onto-Semiotic Approach (OSA) Theory - Muchammad Khafith Octafian Purnomo; Pradnyo Wijayanti (Program Studi S1 Matematika UNESA, 2021)
Mathematics is often associated with a boring subject in the classroom. There’s a need for innovation, especially in the learning process, so students don’t feel bored learning mathematics. One of the innovations available is to connect mathematics with the student's interests. One of the things the students are interested in is animation works, especially anime series. This research aims to explore the mathematical objects in the anime series reviewed from the Onto-Semiotic Approach (OSA) theory. This research is descriptive exploratory research. Data were collected through observation of 5 anime series titles using a research instrument in the form of an observation sheet. The analysis process was carried out on the identified mathematical objects from the 5 anime series titles, then categorizing the identified mathematical objects according to the characteristics of the 6 categories of primary mathematical objects in OSA theory. The results indicate that there are 6 mathematical objects identified as the language category, such as the quadratic equation and trigonometry, 5 mathematical objects identified as the situation category, no mathematical object identified as the concept category, 1 mathematical object identified as the proposition category, 1 mathematical object identified as the procedure category, and 2 mathematical objects as the argument category. The result of this research can be used as an innovation in mathematics learning and as additional research on the use of popular culture in the classroom.